Pengaruh Dividend Per Share Dan Net Profit Margin Terhadap Harga Saham Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Indika, Miki I; Nurbaiti, Nurbaiti; Siregar, Irvan Aswari (Asosiasi Dosen Akuntansi Indonesia, 2022)
This study aims to analyze the effect of dividend per share and net profit margin on stock prices in companies listed on the Indonesia stock exchange. This study uses secondary data, namely data obtained from a second party, namely the Indonesia Stock Exchange. The research hypotheses were tested using descriptive statistics, classical assumption test, and multiple linear regression. The results showed that the Dividend Per Share variable had an effect on the stock price of PT. Astra International Tbk . Net Profit Margin has no effect on the stock price of PT. Astra International Tbk. Based on the results of the F test, F arithmetic > F table is 180.454 > 4.74 with a significance value of 0.000 < 0.05, so it can be concluded that H0 is rejected and H1 is accepted which means that there is a significant effect between Dividend Per Share and Net Profit Margin on Prices Share. Based on the results of the coefficient of determination test, it is known that the value of the coefficient of determination (R2) in this study is 0.981 or 98.1%. Thus the ability of the independent variables consisting of Dividend Per Share and Net Profit Margin can explain the dependent variable of Share Price of 98.1% while the remaining 1.9% is influenced by other variables outside of this study.